CD8+CD57+ T cells exhibit distinct features in human non-small cell lung cancer - Wei Sun; Rong Liu; Bing Huang; Peiliang Wang; Zhiwei Yuan; Jianjian Yang; Hui Xiong; Ni Zhang; Qi Huang; Xiangning Fu; Lequn Li (Journal for ImmunoTherapy of Cancer)
Background The repetitive antigen stimulation during chronic infection often leads to the accumulation of CD8+CD57+ T cells. These cells express high levels of interferon-γ, granzyme B and perforin with elevated cytolytic effect, and are considered as the most potent cells for combating chronical viral infection. The status of CD8+CD57+ T cells in non-small cell lung cancer (NSCLC) has not been well defined.Methods We used flow cytometry and undertook a systemic approach to examine the frequency, immunophenotyping and functional properties of CD8+CD57+ T cells in the peripheral blood, tumor tissue and the corresponding normal tissue, as well as lung draining lymph nodes, of patients with NSCLC.Results CD57+ T cells expressed high levels of programmed cell death-1 (PD-1) in all tested compartments and were predominantly CD8+ T cells. These cells in the peripheral blood displayed a terminally differentiated phenotype as defined by loss of CD27 and CD28 while expressing KLRG1. CD8+CD57+ T cells exhibited enhanced cytotoxic potencies and impaired proliferative capability. Unlike CD57+ T cells in the peripheral blood, a significant proportion of CD57+ T cells in the primary tumors expressed CD27 and CD28. CD8+CD57+ T cells in tumors lacked cytotoxic activity. The proliferative activity of these cells was also impaired. CD8+CD57+ T cells in the corresponding normal lung tissues shared similarities with their counterparts in peripheral blood rather than their counterparts in tumors. The vast majority of CD8+CD57+ T cells in lung draining lymph nodes were positive for CD27 and CD28. These cells were unable to produce perforin and granzyme B, but their proliferative activity was preserved. CD8+CD57+ T cells in tumors displayed an inferior response to PD-1 blockade compared with their CD8+CD57- counterparts. Interleukin (IL)-15 preferentially restored the effector function of these cells. Additionally, IL-15 was able to restore the impaired proliferative activity of CD8+CD57+ T cells in tumors and peripheral blood.Conclusions Our data indicate that the failure of the immune system to fight cancer progression could be a result of impaired CD8+ T-cell functional maturation into fully differentiated effector T cells within the tumor microenvironment. Boosting IL-15 activity might promote tumor-reactive CD8+ T-cell functional maturation while preserving their proliferative activity.